Aspartame Induce Modification in Membrane Bound and Antioxidant Enzymes in Liver and Kidney of Wistar Albino Rats - Kumar Choudhary, Arbind; Selvaraj, Saravanan; Sheela Devi, Rathinasamy (Current Nutrition & Food Science, 2014)
Aspartame is rapidly and completely metabolized in humans and experimental animals to aspartic acid (40%), phenylalanine (50%) and methanol (10%). Methanol, a toxic metabolite is primarily metabolized by oxidation to formaldehyde and then to formate these processes are accompanied by the formation of superoxide anion and hydrogen peroxide. This study focuses on whether the oral administration of aspartame (40 mg/kg.bw/day) for 15-days and 30- days, has any effect on membrane bound ATPase, ‘Marker’ enzymes (ALP, ALT, ACP, AST &LDH) some selective liver and kidney function parameter and antioxidant status in liver and kidney of rats. To mimic human methanol metabolism, folate deficient rats were used. After 15-days of aspartame administration, there was no change observed in kidney, however liver showed a significant decrease in membrane bound ATPase enzyme (Na+/k+, Mg2+ & Ca2+), marker enzymes (ALP, ALT, AST & LDH) and significant increase in marker enzymes (ACP), antioxidant enzyme level. However, after aspartame administration for30-days, liver and kidney both showed a significant decrease in membrane bound ATPase enzyme( Na+k+, Mg2+ & Ca2+), marker enzymes (ALP, ALT, AST & LDH) and decrease of antioxidant enzyme level in liver and significant increase in marker enzymes (ACP) and antioxidant enzyme level in kidney. This study concludes that oral administration of aspartame (40mg/kg.bw/day) for longer duration may induce oxidative stress by aspartame metabolite methanol and can damage both liver and kidney. The liver was found to be more sensitive than kidney to oxidative stress, as also reflected by the histology of liver and kidney.
Keywords: ATPase